PENERAPAN INQUIRY BASED LEARNING UNTUK MENGETAHUI RESPON BELAJAR SISWA PADA MATERI KONSEP DAN PENGELOLAAN KOPERASI - Kusmaryono, Heru; Setiawati, Rokhis (Dinamika Pendidikan, 2013)
The objective of the study was to know the students learning responsestoward Inquiry Based Learning method on the materials of Cooperative Concept andManagement. It was a qualitative descriptive approach and the research subjects were32 students of class X IIS 1 at SMA 1 Bae Kudus. The data were collected byobservation, documentation and interview. The results showed that students gavepositive responses toward the application of Inquiry Based Learning method sincestudentsâ responses were very high at 85.51%.